The Effect of Murottal Al-Qur’an to Decrease Anxiety Level of Pre-Sectio Caesarea Patient - Tia Setriana; Nunu Harison (Minsight: Midwifery Insight and Innovation Journal, 2025)
A cesarean section is a medical procedure that often causes anxiety. Mothers who are about to undergo a cesarean section generally experience varying levels of anxiety, ranging from mild to panic. If not immediately addressed, this anxiety can increase blood pressure and respiration, potentially leading to bleeding both during and after surgery. Involving spiritual aspects is a non-pharmacological way to reduce anxiety. One such method is listening to the recitation of the Qur'an, which serves to bring individuals closer to God, calm them, make them feel protected, and provide a sense of relief. This study aims to determine the effect of Qur'anic murottal therapy on reducing anxiety levels. The research method used is a pre-experimental one-group pre-test post-test design. The subjects of this study are patients scheduled for cesarean section surgery at the Nusa Indah Health Center in Bengkulu. The sample was selected using purposive sampling. Anxiety levels were measured using the HARS scale. Respondents listened to the Qur'anic murottal for 25 minutes. Data analysis was conducted using the Wilcoxon signed-rank test. The results showed that, before listening to the Qur'anic murottal, many experienced severe anxiety, and after listening, there was a decrease in anxiety levels to mild and moderate anxiety. The hypothesis test using the Wilcoxon signed-rank test obtained a P value = 0.000, which means the P value < 0.05, thus H1 is accepted. The conclusion of this study is that Qur'anic murottal can reduce anxiety levels in pre-operative cesarean section patients.